In situ real-time continuous monitoring of soil carbonate ions using a portable CuO–Cu2O-based electrochemical sensor - Yuying Bao; Jingfang Ji; Jiyu Chen; Kaiquan Li; Pan Liu; Jingmin Ge; Ronghan Wei; Xiaodong Lei; Jingwei Zhang (Analytica Chimica Acta, 2026)

Clay mineral evidence for sediment provenance and the evolution of the East Asian Winter Monsoon in the central Philippine Sea over the last 4.38 Ma - Jun Sun; Fei Guo; Huaichun Wu; Wei Huang; Jian Liu; Kai Lu; Jingfang Lu; Shuang Sun; Meinan Shi; Boya Li; Liwei Liu; Xiaoke Qiang (Global and Planetary Change, 2026)

Pupil dynamic adaptation in response to environmental luminance: A controlled laboratory study - Qing Pan; Shoujie Zhang; Jingfang Bian; Tao Luo; Minchen Wei; Peng Xue; Jingchao Xie; Jiaping Liu (Building and Environment, 2026)

The individual and combined effects of coastline changes and riverine input on water quality: A multi-scenario simulation perspective - Jingfang Lu; Wei Zheng; Dehai Song; Xianqing Lv; Weimin Wang; Honghua Shi (Marine Pollution Bulletin, 2025)

Effects of stir-frying frequency on meat quality via multimodal infrared & accelerometer platform - Yibing Yuan; Liangyu Xue; Xiaojia Hu; Guowei Gao; Wenzheng Zhu; Yangjun Wang; Jingfang Hu; Huixin Tian; Chunhui Zhang; Wensong Wei (International Journal of Gastronomy and Food Science, 2025)

Transcriptome sequence reveal the roles of MaGME777 and MabHLH770 in drought tolerance in Musa acuminata - Yuchen Wei; Jingfang Shi; Xueyi Xie; Feng Zhang; Huizhen Dong; Yaoyao Li; Fangcheng Bi; Xiaosan Huang; Tongxin Dou (Plant Science, 2025)

Raw meat 3D laser scanning imaging: Optimized by adaptive contour unit - Lingping Bu; Huixin Tian; Zhen Qiao; Xiaojia Hu; Guowei Gao; Bo Qi; Zhize Wang; Jingfang Hu; Chunhui Zhang; Dequan Zhang; Wensong Wei (Food and Bioproducts Processing, 2025)

Interface engineering of Platinum–Copper alloy/titanium dioxide for enhanced photocatalytic carbon dioxide reduction - Xin Wang; Wei Tan; Bo Peng; Shangcong Sun; Xue Li; Kaiqiang Wang; Jiawei Ji; Haohong Liao; Jingfang Sun; Qing Tong; Haiqin Wan; Lin Dong (Environmental Research, 2024)

Quaternary pollen record and paleoenvironmental evolution of the Bohai Sea strait - Jingfang Lu; Wei Huang; Jun Sun; Feifei Wang; Yuexin Gao; Xin Fan; Daolai Zhang (Regional Studies in Marine Science, 2023)

Distribution of gold derived from hydrothermal fluids on the modern seafloor and its impact on the gold budget of seawater - Wei Huang; Jin Liang; Jingfang Lu; Fanghui Hou; Panfeng Li; Ruyong Cui (Frontiers in Marine Science, 2023)
The modern seafloor hydrothermal system plays a significant role in the cycling of energy and mass between the internal and external layers of the oceanic crust and upper mantle. It continues to supply hydrothermal fluids containing three to five orders of magnitude more gold into the ocean than the amount typically present in deep seawater. It has a considerable impact on the distribution and budget of gold with respect to the large geological inventory of the ocean along with other input sources such as river water. The large amount of various types of data compiled for this study reveals that only about 0.3% of the annual hydrothermal flux of gold (2618.3 kg/a) injected into the overlying seawater column as a dissolved phase is eventually trapped in sulfide deposits near vent sites on the seafloor, while about 0.8% is trapped in metalliferous sediments that fall out from the distal nonbuoyant plume. The remaining ~98.9% of gold is delivered into the depths of the global open ocean. The global budget of gold in seawater (about 1.4 × 10 7 kg), the annual flux of hydrothermal fluids at the seafloor (about 2.6 × 10 3 kg/a), the amount delivered by river water (about 7.2 × 10 4 kg/a), and significant estuarine removal (15%) allows us to estimate the residence time of gold in the modern ocean to be about 220 years. This value is 70% shorter than that (~1000 years) reported previously. In the future, the use of appropriate artificial means to achieve more efficient precipitation of gold from the hydrothermal system at the seafloor could increase the level of enrichment of gold to obtain gold-rich hydrothermal deposits, yielding greater economic benefits.

Hybrids of oxoisoaporphine–tetrahydroisoquinoline: novel multi-target inhibitors of inflammation and amyloid-β aggregation in Alzheimer’s disease - Yusi Chen; Chunlin Su; Li Wang; Jingfang Qin; Shenqi Wei; Huang Tang (Molecular Diversity, 2019)

Transcriptomic analysis reveals the effect of the exopolysaccharide of Psychrobacter sp. B-3 on gene expression in RAW264.7 macrophage cells - Pingping Zhang; Jiang Li; Leiye Yu; Jingfang Wei; Tong Xu; Guojie Sun (Acta Oceanologica Sinica, 2018)

MicroRNA-135b regulates metastasis suppressor 1 expression and promotes migration and invasion in colorectal cancer - Weiyun Wu; Zhuang Wang; Pengchun Yang; Jingfang Yang; Jian Liang; Yuanhong Chen; Hao Wang; Guoli Wei; Shicai Ye; Yu Zhou (Molecular and Cellular Biochemistry, 2014)

Steroidal saponins from the rhizomes of Polygonatum odoratum - Dongmei Wang; Dengwu Li; Wei Zhu; Jingfang Zhang; Pai Peng (Natural Product Research, 2009)